Getting to Know Cross-Border Lease - Liharyanti, Uci; Khaddafi, Muammar (Advances In Social Humanities Research, 2024)
A cross-border lease is a leasing or rental and financing transaction carried out outside the borders of a country where the lessor is domiciled in a different country from the lessee's country. This type of leasing transaction is sometimes referred to as cross-border leasing or international leasing transaction because it involves two different countries. An introduction to this type of leasing includes the advantages and risks of cross-border leasing businesses, an overview of taxes and laws, and implementation and development trends of cross-border leasing businesses. The research methodology used in this study includes a comprehensive analysis of existing literature, case studies of current cross-border lease practices, and interviews with industry experts to understand the practical implications and challenges. Additionally, statistical data on global leasing trends were analyzed to project future developments. It is estimated that cross-border leasing will become increasingly popular, driven by economic globalization and companies' need for financing flexibility. However, stringent regulations will continue to be a challenge for this practice.